2013
DOI: 10.1155/2013/205183
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nanosilver Exposure on Cholinesterase Activities, CD41, and CDF/LIF-Like Expression in ZebraFish (Danio rerio) Larvae

Abstract: Metal nanosolicoparticles are suspected to cause diseases in a number of organisms, including man. In this paper, we report the effects of nanosilver (Ag, 1–20 nm particles) on the early development of the zebrafish, a well-established vertebrate model. Embryos at the midgastrula stage were exposed to concentrations ranging from 100 to 0.001 mg/L to verify the effects on different endpoints: lethality, morphology, expression of cholinergic molecules, and development of the immune system. (1) Relative risk of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 49 publications
2
17
0
Order By: Relevance
“…12 AgNPs have also been shown to inhibit molecules related to the cholinergic system and consequently impair the immune system differentiation in zebrafish. 13 AgNPs behave as allergens in mice, as reported in a recent proteome-based study. 14 The intravenous administration of AgNPs also showed immunotoxicity in murine models.…”
Section: Introductionsupporting
confidence: 70%
“…12 AgNPs have also been shown to inhibit molecules related to the cholinergic system and consequently impair the immune system differentiation in zebrafish. 13 AgNPs behave as allergens in mice, as reported in a recent proteome-based study. 14 The intravenous administration of AgNPs also showed immunotoxicity in murine models.…”
Section: Introductionsupporting
confidence: 70%
“…Any inhibition in AChE activity would prolong motor neuron firing that could adversely modify animal responses and behaviour. Nanosilver has been shown to inhibit AChE activity in zebrafish larvae (Myrzakhanova et al, 2013). This also suggests that owing to their nano size, AgNPs can easily cross blood-brain barrier and affect vital neuronal functions.…”
Section: Biochemical Evaluation Of Neuronal Functionmentioning
confidence: 98%
“…By contrast, sulfidation of AgNPs resulted in a small but significant increment (p<0.05) in brain AChE activity (0.997±0.002 μM acetylthiocholine hydrolyzed/mg protein/min) when compared to fish exposed to non-sulfidated AgNPs. AChE is well recognized as a marker of xenobiotic stress in aquatic organisms and is important for normal neural function (Myrzakhanova et al, 2013). Any inhibition in AChE activity would prolong motor neuron firing that could adversely modify animal responses and behaviour.…”
Section: Biochemical Evaluation Of Neuronal Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not clear if this effect resulted from mechanical perturbation (thigmomorphogenesis) and/or lack of oxygen or mineral uptake (suffocation) due to external (i.e., on the epidermis) TiO 2 -nanoparticles deposition, or from genuine uptake of particles. The tests with aquatic models showed that the effects of exposure to silver nanoparticles induced a trend to the impairment of immune responses, possibly related to the degree of inhibition of the cholinesterases activities [17][18][19][20][21][22]. 4.…”
mentioning
confidence: 99%